Man in his time plays many parts : life stories of William Jordan : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in History at Massey University - Hickey, Carina (Massey University, 2003)
When the first Labour government was elected in 1935 William Jordan became both New Zealand's High Commissioner in London and New Zealand's representative at the League of Nations. Prior to his appointment Jordan had served nearly fourteen years as a Labour Member of Parliament.3 3 Malcolm Templeton, 'Jordan, William Joseph 1879-1959'. Dictionary of New Zealand Biography, updated 19 July 2002 URL: http://www.dnzb.govt.nz/ I first became interested in Jordan while I was completing a research exercise on New Zealand's reactions to the Sino-Japanese war in 1937. Jordan featured prominently at the League of Nations when the New Zealand government's stand on international issues brought it into conflict with British policy. He stood out as a significant figure of this period due to his personality and strength of character. As New Zealand's representative, Jordan spoke powerfully on international morality. His forthright speeches showed his courage, often in the face of pressure from other nations. He delivered speeches that were blunt, simple and often in plain undiplomatic language. Bruce Bennett described his, unpretentious, sincere, yet forceful speeches [which] brought him admiration at a forum noted for caution to the point of cowardice. His very simplicity, which some of his associates despised, was part of his magic.4 4Bruce Bennett, New Zealand's Moral Foreign Policy 1935-1939: The Promotion of Collective Security Through the League of Nations, Wellington: New Zealand Institute of International Affairs, 1988, p.14. Jordan's character and personality seemed distinctive and denoted him as a compelling historical individual. Notwithstanding his unique personality, Jordan was also a national figure in his time. When first appointed he was New Zealand's sole diplomatic representative. By the time of his retirement, after a record fifteen years as High Commissioner in London, he had been the country's best-known representative abroad. I was very intrigued to examine not only Jordan the man but to also explore a broader perspective and see how, as a distinct individual, he interacted within the social, cultural and historical contexts of his time.
Keywords: Jordan, William Joseph 1879-1959; Politicians; Diplomats; New Zealand